PENGARUH PEMBERIAN REWARD TERHADAP MOTIVASI BELAJAR SISWA - Nadiah Nadiah; Niarrofah Niarrofah (STIT Al-Marhalah Al-Ulya Bekasi, 2023)
ABSTRACKThe learning process at the high school level often decreases enthusiasm in the learning process in the classroom. This is due to lack of motivation from outside (extrinsic) and within students (intrinsic), as well as lack of appreciation given by teachers and schools. So that the learning process is less interesting for students, and students feel less appreciated for the results that have been achieved. The impact of this makes students less interested and less enthusiastic about teaching and learning activities. And the targeted results were not achieved. The purpose of this study is to find out how related the provision of rewards so that it can affect learning motivation. The method used in this study is descriptive collerational analytic. And the result of this study is the effect of giving rewards with learning motivation. If you look at the rxy obtained which is 0.439, it turns out to be located between 0.40 – 0.70 based on the guidelines contained in the table. So it can be stated that between the correlation of variable X (Reward) and variable Y (Learning Motivation) is a correlation that is classified as moderate or sufficient. Keywords: Reward, Motivation, Ekstrinsik